Religious Institutions in Japan Responding to Covid-19-Induced Risk and Uncertainty: Some Preliminary Considerations - Cavaliere, Paola (Journal of Religion in Japan, 2021)
Abstract This paper discusses adaptations and alternatives that religious institutions in Japan have formulated to help communities develop the capacity to cope with the crisis and perceived risk generated by Covid-19. Qualitative data and observations of online information were collected between February and June 2020. Guided by a crisis approach, the study explores inward and outward responses that some Japanese religious institutions and their members have enacted. The investigation uses Douglas’ (1994) interpretative model of risk and explores those “thought-styles” that religious institutions have engendered that are conducive to cohesion and stability. Findings show that established and new religions alike swiftly responded to Covid-19-induced safety measures by embracing digital technology to continue their core function as cohesion-providers for their social and spiritual communities. The analysis shows that adjustments toward disembodied religious practices might hold potential to continue beyond current Covid-19-related social restrictions.